Studi Kualitatif Tentang Transparansi dan Akuntabilitas Laporan Keuangan pada Bank Umum Konvensional - Anjeli Roulina Simanjuntak; Yudha Sadry Mezsas Purba; Patar Marulitua Simorangkir; Gebriiella Sitorus; Marianto Yus Siagian; Hamonangan Siallagan (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the level of transparency and accountability in the financial reporting of conventional commercial banks in Indonesia using a qualitative descriptive approach. The research focuses on the processes of preparing, presenting, and disclosing financial statements in accordance with the principles of Good Corporate Governance (GCG). Data were collected through in-depth interviews with bank management, analysis of financial report documents, and a literature review of accounting standards and Financial Services Authority (OJK) regulations. The findings reveal that most conventional banks have made efforts to enhance transparency through adequate financial disclosure; however, there are still limitations in the presentation of relevant non-financial information for stakeholders. Accountability has been implemented through internal and external audit mechanisms, although its effectiveness is still influenced by auditor independence and the quality of oversight by the board of commissioners. This study is expected to contribute to improving financial reporting practices that are more transparent, accountable, and oriented toward public interest within the banking sector.